Weekly exercise does not improve fatigue levels in Parkinson's disease. - Winward, C; Sackley, C; Meek, C; Izadi, H; Barker, K; Wade, D; Dawes, H (2012)
BACKGROUND: Fatigue is one of the most disabling non-motor symptoms for people with Parkinson's disease. Exercise may modify fatigue. This study examines prescribed exercise effects on physical activity levels, well-being, and fatigue in Parkinson's disease. METHODS: In this single-blinded trial, participants were randomly assigned to either a 12 week community exercise program or control group. Primary outcome measures were fatigue (Fatigue Severity Scale) and physical activity. RESULTS: Thirty-nine people with Parkinson's disease were included: 20 in exercise and 19 in control. Sixty-five percent of the study group were fatigued (n = 24, mean 4.02, SD 1.48). Increased fatigue was associated with lower mobility and activity (P < .05). Individuals participated in a mean of 15 (SD 10) exercise sessions with no significant change in fatigue, mobility, well-being, or physical activity after exercise (P ≥ .05). CONCLUSION: Participation in weekly exercise did not improve fatigue in people with Parkinson's Disease.